ANALYSIS OF FACTORS AFFECTING THE ECONOMIC STRATEGY OF DIVERSIFICATION - Taspenova, G.A.; Karipova, A.; Alisheva, D.E. (Academic Journal of Physical and Chemical Sciences, 2018)
The Republic of Kazakhstan, as a country whose goal to be among the 20 countries with developed economies, has become aware of the real realities of new production, the competitiveness of developed transnational corporations, whose production levels need to be achieved and maintained. The relevance of this article lies in the fact that today, advanced companies carry out their growth mainly through diversification, invading other areas, often not having production or functional ties with the mainstream, mastering fundamentally different types of products. The article is devoted to the analysis of factors affecting the economic strategy of diversification, based on the implementation of innovative approaches to management. The article shows that today there is no single strategy by which performance optimization can be achieved and the competitive cost of products achieved. A comparative analysis of the diversification policy in Kazakhstan highlights the reasons why the implementation of such approaches is essential for the development of a competitive economy. When writing the article, general scientific methods of cognition (statistical, normative analysis, synthesis, analogy, generalization), empirical-theoretical (collection, study and comparison of data), as well as methods of scientific cognition (historical-legal, formal-logical, systemic, relatively -legal). In processing and systematizing the data, grouping and classification methods were used. The information and statistical base of the study was compiled from official periodical and information and analytical publications of the Republic of Kazakhstan